The system of the circular review for vehicles based on ultra-wideband sensors - S. V. Shishanov; A. V. Myakinkov (Известия высших учебных заведений России: Радиоэлектроника, 2015)
Configuration of the radar system circular view for vehicles based on ultra-wideband sensors is proposed. The algorithms of coordinate determination are considered. The estimations of coordinate measurement accuracy are obtained.